Evaluation of bio-materials’ rejuvenating effect on binders for high-reclaimed asphalt content mixtures - Jiménez del Barco Carrión, Ana; Perez-Martinez, M.; Themeli, A.; Lo Presti, Davide; Marsac, P.; Pouget, Simon; Hammoum, F.; Chailleux, Emmanuel; Airey, Gordon (Consejo Superior de Investigaciones Científicas, 2017)
The interest in using bio-materials in pavement engineering has grown significantly over the last decades due to environmental concerns about the use of non-recoverable natural resources. In this paper, bio-materials are used together with Reclaimed Asphalt (RA) to restore some of the properties of the aged bitumen present in mixtures with high RA content. For this purpose, two bio-materials are studied and compared to conventional and polymer modified bitumens. Blends of these materials with RA bitumen were produced and studied to simulate a 50% RA mixture. The rejuvenating effect of the two bio-materials on RA has been assessed and compared with the effect of the conventional binders. Apparent Molecular Weight Distribution of the samples (obtained by the ?-method) and different rheological parameters were used for this purpose. Results revealed the power of bio-materials to rejuvenate RA bitumen, showing their capability to be used as fresh binders in high-RA content mixtures.